Analisa Tingkat Kepuasan Penggunaan E-learning Pada SMAN 2 Lahat Menggunakan Metode EUCS (End User Computing Satisfactionm) - Yosita fadila Yosita; Nia Oktaviani (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
In carrying out its a activities ,SMAN 2 Lahat is Under the auspices of the ministry of Education and Culture.The school provides internet acces facilities that can be used to support teaching and learning activitties more easily.And SMAN 2 Lahat is one of the schools that has e-learning to support learning needs.End User Computing Satisfaction (EUCS) is a method used to measure the satisfaction level of user .In this study,5 EUCS indicators were measure which would determine the level of satisfaction of E-Learning users,namely content,accuracy,form ease of use and timeliness.Fron the results of this study if was found that the content variable satisfaction level was at 82% the accuracy variable satisfaction level was at 83%,the format variable satisfaction level was at 89%,the ease of use variable satisfaction level was at 87% the satisfaction level the timeless variable is at 88%,for the level of user satisfaction with E-Learning at SMAN 2 Lahat as a whole it is at 84%,that is,users are satisfied.For the level of satisfaction of E-learning as a whole is at 84% namely satisfied.